The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.brat.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory retrieval and appraisal in social anxiety disorder

Abstract: Individuals with social anxiety disorder (SADs; n = 41) and healthy controls (HCs; n = 40) were administered the Waterloo Images and Memories Interview, in which they described mental images that they tend to experience in both anxiety-provoking and non-anxiety-provoking social situations. Participants then recalled, in as much detail as possible, specific autobiographical memories of salient aversive and non-aversive social experiences that they believed led to the formation of these images. Audio-recorded me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 80 publications
1
28
1
Order By: Relevance
“…Though the literature on episodic memory biases in SA is characterised by varied methodological approaches (Morgan, 2010;Zlomuzica et al, 2014), some studies have found that high SA individuals exhibit enhanced memory for social threat information, such as negative words or critical facial expressions (e.g., Lundh & Ӧst, 1996;Mansell & Clark, 1999). Similarly, studies of memory for autobiographical past events have demonstrated that higher trait SA is associated with elevated retrieval of threatening and highly emotional material (Krans, de Bree, & Bryant, 2013;Moscovitch et al, 2018;Wenzel & Cochran, 2006). Moscovitch et al (2018) found that while participants with SAD and healthy controls could retrieve autobiographical memories of both aversive and non-aversive social experiences with similar ease, SAD participants' memories of negative events contained greater episodic detail (i.e., more specific information about those particular negative experiences) than memories of negative events that were retrieved by controls; however, there were no such differences between groups for memories of non-aversive past events.…”
Section: Introductionmentioning
confidence: 99%
“…Though the literature on episodic memory biases in SA is characterised by varied methodological approaches (Morgan, 2010;Zlomuzica et al, 2014), some studies have found that high SA individuals exhibit enhanced memory for social threat information, such as negative words or critical facial expressions (e.g., Lundh & Ӧst, 1996;Mansell & Clark, 1999). Similarly, studies of memory for autobiographical past events have demonstrated that higher trait SA is associated with elevated retrieval of threatening and highly emotional material (Krans, de Bree, & Bryant, 2013;Moscovitch et al, 2018;Wenzel & Cochran, 2006). Moscovitch et al (2018) found that while participants with SAD and healthy controls could retrieve autobiographical memories of both aversive and non-aversive social experiences with similar ease, SAD participants' memories of negative events contained greater episodic detail (i.e., more specific information about those particular negative experiences) than memories of negative events that were retrieved by controls; however, there were no such differences between groups for memories of non-aversive past events.…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed various measures at an initial session, including the SPIN and DASS. Additional measures that were not relevant to the present study were also administered in the initial session, as detailed in Moscovitch et al (2018). 1 One week after the initial session, participants attended the training session.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Negative images are often rooted in distressing autobiographical memories in which the themes of recollected events evoke central features of each specific disorder (Hirsch & Holmes, 2007; Holmes, Geddes, Colom, & Goodwin, 2008; Romano, Ma, Moscovitch, & Moscovitch, In Press). In SAD, it is common for individuals to experience distressing images of themselves appearing socially inept and undesirable and to associate the formation of such images with past experiences of perceived social failure or humiliation (Moscovitch, 2016; Moscovitch et al, 2018). Despite being excessively negative and distorted, these images of the self are believed by socially anxious individuals to represent accurate portrayals of how they appear to others (Hackmann, Clark, & McManus, 2000; Moscovitch, Gavric, Merrifield, Bielak, & Moscovitch, 2011; Stopa & Bryant, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the former seem essential for high-fidelity representation of personally experienced events, the latter rather contribute to the coherence and continuity of self-knowledge and identity through time (Levine et al, 2002). To date, the AI scoring scheme has been used in a wide range of studies related to memory processes in aging (e.g., Levine et al, 2002), psychiatric conditions (e.g., Moscovitch et al, 2018), neurodegeneration (e.g., Bastin et al, 2013) or lesion cases (e.g., Steinvorth et al, 2005). However, no study has yet investigated the episodic and semantic composition of NDE verbal recollections as well as the comparison with those of flashbulb memories.…”
Section: Introductionmentioning
confidence: 99%